A LITERATURE REVIEW OF DOMESTIC VIOLENCE (DV): CAUSAL FACTORS, VICTIMS, AND IMPACTS - Dewi Hestiani K; Eka Wahyuni Amiruddin; Muh. Saleh (Media Inovasi Pendidikan dan Publikasi, 2023)
Domestic violence, including physical, sexual, psychological, and neglect violence. Domestic violence often occurs due to an unbalanced relationship between spouses, influenced by various factors such as the wife's basic education, husband's religiosity, infidelity, and husband's personality. Domestic violence can also occur due to unhealthy behaviors such as smoking or drinking, husband's personality disorder, low economy, and also the influence of marital status factors. Victims of domestic violence are often women and children. Domestic violence has significant negative impacts, including impacts on the physical and mental health of victims, as well as social and economic impacts. Domestic violence can also disrupt harmony in the family and society. Addressing domestic violence involves various parties, including law enforcement and government and non-government organizations. Legal protection for victims of domestic violence includes assistance in reporting cases, as well as providing criminal sanctions for perpetrators. However, there are still many obstacles in handling domestic violence, including the reluctance of victims to tell the full story and incomplete files. In addition, many domestic violence cases are not handled in accordance with the Law on the Elimination of Domestic Violence and are only handled through mediation. Therefore, this study emphasizes the importance of raising public awareness about domestic violence and the need for effective solutions to prevent and deal with domestic violence.